INFLUENCE OF MASS MEDIA ON THE RESIDENTS OF GAINDAKOT, NEPAL DURING THE COVID-19 PANDEMIC - Kandel, Suresh; Ghimire, Harishchandra; Adhikari, Kishor; Krishna Sharma, Hari; Karn, Abhishek; Sharma, Narayan (Journal of Chitwan Medical College, 2024)
Background: Effective communication during health crises is vital, yet the widespread distribution of information via diverse channels has led to an “infodemic,” propagating misinformation and malpractices adoption. This study aimed to examine the influence of mass media in the adoption of precautionary behavior, and the spreading of fear and panic during the COVID-19 pandemic. Methods: A cross-sectional study was undertaken in Gaindakot, Nepal, encompassing individuals aged 18-59. Face-to-face interviews employing a structured questionnaire were employed to collect data from 380 participants selected through a multistage systematic random sampling method. The collected data underwent through SPSS version 20, for descriptive statistics, and bivariate and multivariate analyses. Results: More than two-thirds (69.2%) of the respondents demonstrated a high level of adopting precautionary measures, while 43.2% of participants reported feeling fear and panic due to information from mass media. Social media (61.6%) and television (32.9%) were identified as the primary sources of information during the COVID-19 pandemic. Precautionary behavior adoption was significantly associated with ethnicity, income, and access to mass media while the spreading of fear and panic was significantly associated with sex, marital status, and employment status of the respondent. Conclusions: Mass media plays a significant role in shaping public perceptions and behaviors during public health emergencies. This study recommends that accurate and targeted media messaging is crucial to promoting desirable health behaviors and reducing misinformation.